Dental Polymeric Composites: A Narrative Review of Properties and Clinical Performance - Ahmed, Dina; Al-Ani, Ahmed; Yousif, Eamd (Indonesian Dental Association, 2025)
Introduction: Synthetic and natural polymers have attracted significant interest due to their adaptability and wide use in biomedical sciences. Their chemical and physical properties can be tailored to meet specific requirements, making them essential in the development of advanced healthcare solutions. Objective: The objective of this narrative review is to highlight the biomedical applications of polymers, with particular emphasis on the dental field, while assessing their stability, degradation, and bioactivity. Methods: Relevant literature was analyzed to examine recent developments in polymer modification, functional performance, and biomedical utility. Results: Results show that polymers are not restricted to biomaterial applications but also play a vital role in drug delivery systems, where stability and degradation behavior are crucial for maintaining bioactivity. Conclusion: Polymers represent indispensable tools in biomedical sciences, with dentistry and drug delivery systems offering promising avenues for future research and clinical practice.